(untitled) (Educational Dimension, 2022)
The role of information and communication technology as well as teaching aids in specialized chemistry instruction was examined in the article. One of the key outcomes of specialized instruction in chemistry is the development of research skills in high school students. To ensure conformity with the principles of specialized chemistry teaching, ICT tools have been analyzed and systematized. The decision to use ICT tools to implement specialized chemistry training and strengthen the research skills of high school students in specialized chemistry training had supported. The findings of a study to assess the feasibility of implementing certain ICT tools to strengthen the research skills of high school students in specialized chemistry training are provided.